A systematic mini-review of epigenetic mechanisms associated with electroconvulsive therapy in humans - Castro, Sayra Catalina Coral; Bicca, Carla; Bicca, Bruno; Araujo, Stéfany; Viola, Thiago Wendt (Frontiers in Human Neuroscience, 2023)
Introduction Electroconvulsive therapy (ECT) is one of the most effective strategies for treating resistant major depression. Although the mechanism of action is not fully understood and studies are limited, epigenetics is a promising area for the development of biomarkers associated with ECT treatment response. Aim We reviewed studies available in the literature that explored the epigenetics of ECT in peripheral samples from patients with major depressive disorder (MDD). Methods A systematic review was performed following The PRISMA guidelines. The search was performed in seven electronic databases: Scopus, Web of Science, Medline, PsycINFO, Embase, Cochrane, and Cinahl. Results Nine studies were included. Seven assessed DNA methylation and three investigated microRNAs (miR). Overall, most studies were exploratory, with small sample sizes, and we found high heterogeneity between the study’s design, ECT protocols, molecular biology methods, and epigenetic findings. Investigated candidates with some evidence of association with ECT treatment response were BDNF, S100A10, RNF213M, TNKS, FKBP5, miR-126, miR-106a, and miR-24. Conclusion The present findings seem to support previous preclinical research, suggesting that epigenetic mechanisms play an important role in the molecular mechanism underlying ECT effects.